Clinical characteristics and risk factors associated with diverse manifestations of COVID-19 in patients aged 85 years and older - Xu, Zao-Xian; Yang, Yi; Xin, Shang-Ping; Shou, Xiao-ling (Frontiers in Public Health, 2024)
Objective: The goal of this study is to assess the clinical attributes exhibited by patients aged 85 years and older who present different manifestations of COVID-19, and to examine the factors influencing the classification of the disease severity. Method: This retrospective study was conducted at a single center, encompassing an analysis of clinical data obtained from patients with COVID-19 admitted to a general geriatric hospital in Hangzhou, Zhejiang, China, during the period from December 20, 2022, to February 1, 2023. The study focused on 91 eligible patients whose disease severity was compared based on the imaging findings. Results: A total of 91 patients aged 85 years and older, with a median age of 92, including 46 males, 10 exhibiting mild symptoms, 48 moderate cases, and 33 severe cases met the inclusion criteria. Notably, disease severity displayed a significant correlation with age (p < 0.011). All patients presented with complicated chronic underlying conditions and a history of prolonged medication use. Rheumatic immune diseases (p = 0.040) and endocrine medications, primarily hypoglycemic agents (p = 0.034), exhibited statistical significance. Additionally, markers such as lactate dehydrogenase (LDH) (p = 0.030), interleukin 6 (IL-6) (p = 0.014), and D-dimer (p = 0.007) revealed significant associations with disease severity. Chest computed tomography scans predominantly revealed inflammatory features (n = 81, 89.0%). Notably, patients classified as having mild or moderate conditions exhibited eventual improvement, while 13 patients (39.4%) among the severe cases succumbed to the disease. Conclusion: The classification of disease among patients aged 85 years or older old is correlated with advanced age, concurrent rheumatic immune diseases, and prolonged administration of endocrine medications. Furthermore, patients with elevated levels of LDH, IL-6, and D-dimer demonstrated a higher propensity for developing severe diseases.